A study of multisubstituted chain transfer agents on the kinetics of homopolymerisation of methylmethacrylate . - Dhari Abdullah (College of Education for Pure Sciences, 2013)
ABSTRACT :         A continuation to a previous study of monosubstiuted transfer agents, carried out by the same author, this investigation had been done. It has been found that multisubstituted chain transfer agents, such as tricholoro acetic acid, Di and Tribromo acetic acid, have played a significant role in the reduction of both the rate of polymerization and the molecular weights obtained of the homopolymers of methylmethacrylate, other vinylic monomers such as styrene, showed the same behavior, though they differ in their chemical nature especially that involved their stability due to the resonance effect .